A Ni-M single atom alloy catalyst and its preparation method and application

Ni-M single-atom alloy catalyst was prepared by supporting Ni and precious metals or non-precious metals on a magnesium-aluminum metal mixed oxide support, which solved the problem of insufficient selectivity and stability of existing Ni catalysts in TAP synthesis, and achieved efficient and selective catalytic effect.

CN117654545BActive Publication Date: 2025-03-14EAST CHINA UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311685808.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-11
Publication Date
2025-03-14
Estimated Expiration
2043-12-11

AI Technical Summary

Technical Problem

The existing supported single metal Ni catalysts have low selectivity and stability problems in the catalytic hydrogenation of 2,6-diamino-3,5-dinitropyridine, resulting in limited industrial production of TAP.

Method used

A Ni-M single atom alloy catalyst was developed, using the magnesium-aluminum metal mixed oxide MgAlOX as a support to support the first metal Ni and the second metal M. The second metal M was selected from noble metals or non-precious metals, and was loaded in the form of a single atom, and prepared by co-precipitation method and thermal reduction method.

Benefits of technology

The catalytic effects of mild reaction conditions, high catalytic activity, high reactant conversion rate, high product selectivity and long service life are achieved, and the selectivity and stability of existing catalysts are overcome.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004597625540000171
    Figure BDA0004597625540000171
  • Figure BDA0004597625540000181
    Figure BDA0004597625540000181
  • Figure HDA0004597625560000011
    Figure HDA0004597625560000011
Patent Text Reader

Abstract

The present invention provides a Ni-M single-atom alloy catalyst and a preparation method and application thereof. The catalyst is a magnesium-aluminum metal mixed oxide MgAlO X As a carrier, a first metal Ni and a second metal M are loaded, wherein the second metal M is selected from one of the noble metals Pt, Ru, Pd, Rh, Ir, Ag and Au, or one of the non-noble metals Fe, Co, Cu, Zn, Ga, In, Mn, Bi, Cd, Sn. By configuring a mixed metal salt solution of Ni, M, Mg, and Al, a Ni / M / Mg / Al quaternary layered hydroxide material Q is prepared by a coprecipitation method, and then a supported Ni-M single-atom alloy catalyst is obtained by thermal reduction. The catalyst is used in the reaction of selective hydrogenation of 2,6-diamino-3,5-dinitropyridine to prepare 2,3,5,6-tetraaminopyridine, and shows high activity and high selectivity under mild conditions, avoiding the occurrence of side reactions such as excessive hydrogenation under high temperature conditions; it also has the characteristics of good stability, reusability and long life, and has broad prospects in industrial applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts, and specifically relates to a Ni-M single-atom alloy catalyst used in the selective hydrogenation of 2,6-diamino-3,5-dinitropyridine to prepare 2,3,5,6-tetraaminopyridine and a preparation method thereof. Background Art

[0002] High-performance fibers are a new generation of materials in the fiber field with unique properties. Their development is driven by specific application needs to meet the requirements of different application scenarios. Therefore, they occupy an important position in the fiber field. Among them, poly(p-phenylene benzobisoxazole) (PBO) fibers were once hailed as the super fibers of the 21st century. However, the sensitivity of PBO fibers to sunlight, especially ultraviolet rays (UV), leads to the degradation of the structure and performance of PBO fibers and their composites, which seriously affects the safety and reliability of the use of PBO fiber composites. The poly(2,5-dihydroxy-1,4-phenylene pyridine diimidazole) fiber (PIPD fiber) developed by the Sikkema team of Akzo Nobel in the Netherlands makes up for the shortcomings of PBO in compressive strength, has excellent mechanical properties, stability and adhesion, and is regarded as the best material in the fiber field. However, despite the excellent performance of PIPD fibers, their commercial application scale is still limited, mainly because the synthesis of PIPD monomers is experimentally challenging, especially the synthesis of 2,3,5,6-tetraaminopyridine (TAP) monomers.

[0003] The synthesis method of TAP usually adopts the nitro catalytic reduction method, that is, 2,6-diamino-3,5-dinitropyridine (DADNP) is used as the raw material to synthesize TAP through a selective hydrogenation reaction. This process often requires the use of anhydrous ammonium formate, divalent iron halide salts, divalent tin halide salts and other substances as reducing agents. In recent years, with the continuous progress of heterogeneous catalyst research, Ni-based catalysts have attracted attention in the catalytic hydrogenation of 2,6-diamino-3,5-dinitropyridine (DADNP). However, the supported single metal Ni catalyst has a strong adsorption capacity for the product 2,3,5,6-tetraaminopyridine (TAP), which easily leads to excessive hydrogenation, thereby reducing its selectivity. In addition, the stability problem of supported single metal Ni catalysts also limits the industrial production of TAP.

[0004] In summary, it is necessary to develop a new and efficient Ni-based catalyst to overcome the above problems, which is of great significance in the field of fiber science and engineering. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a Ni-M single-atom alloy catalyst for selective hydrogenation of 2,6-diamino-3,5-dinitropyridine to prepare 2,3,5,6-tetraaminopyridine, which has mild reaction conditions, good catalytic activity, high reactant conversion rate, high product selectivity and long service life, and a preparation method thereof.

[0006] The first object of the present invention is to provide a Ni-M single atom alloy catalyst, wherein the catalyst carrier is a magnesium-aluminum metal mixed oxide MgAlO X , and load a first metal Ni and a second metal M thereon; the second metal M is selected from one of the precious metals Pt, Ru, Pd, Rh, Ir, Ag and Au, or one of the non-precious metals Fe, Co, Cu, Zn, Ga, In, Mn, Bi, Cd, Sn; the second metal M is loaded on the carrier in the form of a single atom.

[0007] The present invention is further configured that, in the Ni-M single-atom alloy catalyst, the loading amount of the active component first metal Ni is 1wt% to 30wt%, preferably 1wt% to 15wt%, 7wt% to 15wt% or 7wt% to 10wt%, more preferably 10wt%. The loading amount of the second metal M is 50ppm to 1wt%.

[0008] Furthermore, when M is selected from the above-mentioned precious metals, the Ni-M single-atom alloy catalyst is a Ni-Pt, Ni-Ru, Ni-Pd, Ni-Rh, Ni-Ir, Ni-Ag or Ni-Au precious metal single-atom alloy catalyst; the loading amount of the second metal M is 50ppm~0.5wt%; preferably 50ppm~0.1wt%, 100ppm~900ppm or 500ppm~900ppm; more preferably 500ppm.

[0009] Furthermore, when M is selected from the above-mentioned non-precious metals, the Ni-M single-atom alloy catalyst is Ni-Fe, Ni-Co, Ni-Cu, Ni-Zn, Ni-Ga, Ni-In, Ni-Mn, Ni-Bi, Ni-Cd or Ni-Sn non-precious metal single-atom alloy catalyst; the loading amount of the second metal M is 0.1wt% to 1wt%; preferably 0.1wt% to 0.5wt%; more preferably 0.5wt%.

[0010] The second object of the present invention is to provide a method for preparing the Ni-M single-atom alloy catalyst which is simple to operate and has low industrial production cost, and to prepare different types of single-atom alloy catalysts which have the characteristics of high catalyst activity, high selectivity for 2,3,5,6-tetraaminopyridine and long life. The preparation method comprises the following steps:

[0011] (1) using metal salts of Ni, M, Mg, and Al as metal precursors to prepare a mixed metal salt solution; wherein the second metal M is selected from one of the noble metals Pt, Ru, Pd, Rh, Ir, Ag, and Au, or one of the non-noble metals Fe, Co, Cu, Zn, Ga, In, Mn, Bi, Cd, and Sn;

[0012] (2) adding the mixed metal salt solution to a precipitant, and preparing a Ni / M / Mg / Al quaternary layered hydroxide material Q by a coprecipitation method;

[0013] (3) The Ni / M / Mg / Al quaternary layered hydroxide material Q is thermally reduced to obtain a supported Ni-M single atom alloy catalyst.

[0014] The present invention is further configured that, in the step (1), the metal salts of Ni, Mg and Al are nickel nitrate hexahydrate, magnesium nitrate hexahydrate and aluminum nitrate nonahydrate respectively; the precursor species of the second metal M is selected from H2PtCl4, RuCl3, Fe2(SO4)3, Co(NO3)2·6H2O, Cu(NO3)2, ZnCl2, Ga(NO3)3·xH2O, PdCl2, RhCl3·3H2O, C 12 H 18 Ir3O 13 ·C2H3O2·3H2O, In(NO3)3, AgNO3, AuCl4H, Mn(NO3)2, Bi(NO3)3, Cd(NO3)2·4H2O, SnCl2, Na2[PtCl6]·6H2O, N4O 10 One or more of Ru, C2H4N4O6Pd.

[0015] The present invention is further configured such that, in the step (1), the content of Ni in the mixed metal salt solution is 1wt% to 30wt%, and the content of M is 50ppm to 1wt%.

[0016] Furthermore, the content of Ni in the mixed metal salt solution is preferably 1wt% to 15wt%, 7wt% to 15wt% or 7wt% to 10wt%; more preferably 10wt%; when the M is selected from precious metals, the content of M is preferably 50ppm to 0.5wt%; preferably 50ppm to 0.1wt%, 100ppm to 900ppm or 500ppm to 900ppm; more preferably 500ppm; when the M is selected from non-precious metals, the content of M is preferably 0.1wt% to 1wt%; preferably 0.1wt% to 0.5wt%; more preferably 0.5wt%.

[0017] The present invention is further configured that in the step (2), a pH regulator and the mixed metal salt solution are added to the precipitant at the same time under stirring conditions, the temperature of the reaction system is maintained at 60 to 70° C., and the pH value of the reaction system is controlled to be 10±0.5; after the addition is completed, the stirring reaction is continued for 18 to 36 hours, and finally the Ni / M / Mg / Al quaternary layered hydroxide material Q is obtained by filtering, washing and drying.

[0018] Further, the precipitant is selected from Na2CO3 solution, NaHCO3 solution, K2CO3 solution or KHCO3 solution; the pH adjuster is selected from NaOH solution, NH3·H2O or KOH solution. Preferably, the precipitant used is Na2CO3 solution.

[0019] The present invention is further configured such that, in the step (3), the temperature of the thermal reduction is 600 to 950° C., the reduction time is 2 to 10 hours, and the reduction gas is pure hydrogen.

[0020] It should be noted that the temperature of the thermal reduction is reasonably selected within the range of 600 to 950°C according to the different peak positions of H2-TPR, and the time of the reduction reaction is appropriately adjusted within 2 to 10 hours according to the selected reduction temperature. On this basis, it is also possible to appropriately extend the reaction time.

[0021] Preferably, the temperature of the thermal reduction is 650-850°C; more preferably, the temperature of the thermal reduction is 850°C.

[0022] The present invention is further configured such that the Ni / M / Mg / Al quaternary layered hydroxide material Q in step (3) is first subjected to an ion exchange step and then to a thermal reduction step. Specifically, the Ni / M / Mg / Al quaternary layered hydroxide material Q is added to an ion exchanger, stirred at room temperature for a period of time, filtered, washed, dried, and then subjected to a thermal reduction step to obtain a supported Ni-M single atom alloy catalyst.

[0023] Further, the ion exchanger is selected from Na2CO3 solution, NaHCO3 solution, K2CO3 solution or KHCO3 solution. Preferably, the ion exchanger used is Na2CO3 solution.

[0024] The third object of the present invention is to provide an application of the Ni-M single-atom alloy catalyst in the selective hydrogenation of 2,6-diamino-3,5-dinitropyridine to prepare 2,3,5,6-tetraaminopyridine.

[0025] Furthermore, the reaction temperature for the selective hydrogenation of 2,6-diamino-3,5-dinitropyridine to prepare 2,3,5,6-tetraaminopyridine is 25-100° C., and the hydrogen pressure is 0.25-10 MPa.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The present invention provides a Ni-M single-atom alloy catalyst with an orderly and stable structure and a controllable preparation method thereof. The metal salts of Ni, M, Mg and Al are used as metal precursors, and a Ni / M / Mg / Al quaternary layered hydroxide material is prepared by a coprecipitation method. Different types of Ni-M single-atom alloy materials are prepared by adjusting the ratio and elements of the two components Ni and M; and combined with a subsequent thermal reduction process, different types of Ni-M single-atom alloy catalysts can be prepared in a controllable manner. The geometric isolation and electronic interaction between metal Ni and M can regulate the adsorption strength of each species during the reaction, and further regulate the product selectivity.

[0028] It is worth noting that when the single-atom alloy is prepared by the electrochemical replacement method, it mainly relies on the metal with a lower oxidation potential to oxidize the metal ion with a higher oxidation potential. However, the electrochemical replacement reaction can only occur between specific metals, and when the single-atom metal is introduced, it becomes more difficult to complete the replacement when the concentration is low. On the contrary, the coprecipitation method of the present invention is a one-step method, which can realize the preparation of single-atom alloys in a unified loading process, and has the characteristics of flexible regulation of the load range, making it possible to achieve low load. In addition, the synthesis of single-atom alloy catalysts by coprecipitation has the advantages of simple operation, flexible regulation of the second metal species, low cost, and adaptability to mass production, and is more suitable for industrial-scale applications.

[0029] (2) Relative to the hydrogenation reactions of other nitro compounds, pure Ni catalysts show higher conversion rates and selectivity in many cases. However, in the hydrogenation reaction of nitropyridines, the performance of pure Ni catalysts is not ideal, mainly because aminopyridine cannot desorb quickly, resulting in continued hydrogenation of the pyridine functional group. The present invention introduces a second metal M as a single-atom catalyst anchored on the metal surface for this type of reaction, which can change the local electronic environment, thereby achieving faster desorption from the metal surface after nitropyridine is hydrogenated to aminopyridine. This regulation process helps to improve the catalytic efficiency. Such a design strategy aims to overcome the limitations of pure Ni catalysts in the hydrogenation reaction of nitropyridine compounds, thereby achieving more efficient catalytic conversion.

[0030] Through DFT calculation, it is found that compared with Ni, the Ni-M single-atom alloy catalyst of the present invention shows that the adsorption of the reactant DADNP on its surface is significantly enhanced, while the adsorption of the reaction product TAP on its surface is significantly weakened. For example, the adsorption intensity of TAP on the NiPt (111) surface is reduced by about 30% compared with that on the Ni (111) surface. This is caused by the different electronic properties of amino and nitro groups. As an electron-rich group, nitro groups are more likely to be adsorbed on electron-deficient sites, while amino groups are the opposite.

[0031] In summary, the preparation method of the Ni-M single-atom alloy catalyst of the present invention is simple, easy to operate, and has low production cost; at the same time, the catalyst has the characteristics of high catalytic activity, good selectivity, and long life, and is stable, recyclable, and reusable; the reaction conditions for selective hydrogenation of 2,6-diamino-3,5-dinitropyridine to prepare 2,3,5,6-tetraaminopyridine using the catalyst are mild, and complete conversion can be achieved in a relatively low temperature range, thereby avoiding excessive hydrogenation of 2,3,5,6-tetraaminopyridine under high temperature conditions, and is environmentally friendly, showing broad industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 HRTEM image of the Ni-Pt single atom alloy in Example 1 and the corresponding EDS mapping image.

[0033] Figure 2 EXAFS spectra of the Fourier transform of the Pt L3 edge of the Ni-Pt single atom alloy in Example 1 and the Pt-LDH in Comparative Example 2. DETAILED DESCRIPTION

[0034] The technical scheme of the present invention is clearly and completely described below with specific embodiments. It should be understood that the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention. Unless otherwise defined, all professional and scientific terms used in the text have the same meanings as those familiar to those skilled in the art.

[0035] As used herein, "room temperature" refers to 10-30° C., preferably 20-25° C. The content is the Ni content and M content in the solution during the preparation process.

[0036] Example 1

[0037] First, 100 mL of 0.4 mol / L Na2CO3 aqueous solution was added to a three-necked flask, and then four metal salts Ni(NO3)2·6H2O, H2PtCl4, Mg(NO3)2·6H2O and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water (referred to as solution A). In the quaternary metal salt solution, the content of Ni was 10 wt%, the content of Pt was 500 ppm, and (Ni 2+ +Mg 2+ ):Al 3+ The molar ratio is 3: 1. At the same time, 250 mL of a 0.4 mol / L NaOH solution (referred to as solution B) was also prepared.

[0038] Solution A and solution B were slowly added to the three-necked flask at the same time and stirred vigorously. During the mixing process, the temperature was maintained at 65°C and the pH of the solution was maintained at 10±0.5. After the addition was completed, the temperature of the reaction solution was maintained at 65°C and continued to be stirred for 16 hours, then filtered and washed with ultrapure water several times until the pH value of the washing solution was 7. The sample was then dried in still air at 100°C for 12 hours. The dried sample was immersed in a 2mol / L Na2CO3 solution at room temperature and stirred for 16 hours. Finally, the sample obtained after filtration and drying was reduced at 850°C for 4 hours under pure hydrogen conditions to obtain a Ni-Pt single-atom alloy catalyst.

[0039] like Figure 1 As shown, Pt species are highly dispersed on the catalyst surface, combined with Figure 2 , The EXAFS spectrum analysis of the Fourier transform of the Pt L3 edge of the Ni-Pt single-atom alloy shows that the Pt species in NiPt coordinates with the Ni species, and there is a peak of the Pt-Ni coordination bond, but no peak of the Pt-Pt coordination bond, indicating that the Pt species in the prepared catalyst exists in the form of a single atom.

[0040] Example 2

[0041] First, 100 mL of 0.4 mol / L Na2CO3 aqueous solution was added to a three-necked flask, and then four metal salts Ni(NO3)2·6H2O, Na2[PtCl6]·6H2O, Mg(NO3)2·6H2O, and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water (referred to as solution A). In the quaternary metal salt solution, the content of Ni was 15 wt%, the content of Pt was 500 ppm, and (Ni 2+ +Mg 2 + ):Al 3+ The molar ratio is 3: 1. At the same time, 250 mL of a 0.4 mol / L NaOH solution (referred to as solution B) was also prepared.

[0042] Solution A and solution B were slowly added to the three-necked flask at the same time and stirred vigorously. During the mixing process, the temperature was maintained at 65°C and the pH of the solution was maintained at 10±0.5. After the addition was completed, the temperature of the reaction solution was maintained at 65°C and continued to be stirred for 16 hours, then filtered and washed with ultrapure water several times until the pH value of the washing solution was 7. The sample was then dried in still air at 100°C for 12 hours. The dried sample was immersed in a 2mol / L Na2CO3 solution at room temperature and stirred for 16 hours. Finally, the sample obtained after filtration and drying was reduced at 850°C for 4 hours under pure hydrogen conditions to obtain a Ni-Pt single-atom alloy catalyst.

[0043] Example 3

[0044] First, 100 mL of 0.4 mol / L Na2CO3 aqueous solution was added to a three-necked flask, and then four metal salts Ni(NO3)2·6H2O, RuCl3, Mg(NO3)2·6H2O and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water (referred to as solution A). In the quaternary metal salt solution, the content of Ni was 10 wt%, the content of Ru was 800 ppm, and (Ni 2+ +Mg 2+ ):Al 3+ The molar ratio is 3: 1. At the same time, 250 mL of a 0.4 mol / L NaOH solution (referred to as solution B) was also prepared.

[0045] Solution A and solution B were slowly added to the three-necked flask at the same time and stirred vigorously. During the mixing process, the temperature was maintained at 65°C and the pH of the solution was maintained at 10±0.5. After the addition was completed, the temperature of the reaction solution was maintained at 65°C and continued to be stirred for 16 hours, then filtered and washed with ultrapure water several times until the pH value of the washing solution was 7. The sample was then dried in still air at 100°C for 12 hours. The dried sample was immersed in a 2 mol / L Na2CO3 solution at room temperature and stirred for 16 hours. Finally, the sample obtained after filtration and drying was reduced at 850°C for 4 hours under pure hydrogen conditions to obtain a Ni-Ru single atom alloy catalyst.

[0046] Example 4

[0047] First, 100 mL of 0.4 mol / L Na2CO3 aqueous solution was added to a three-necked flask, and then four metal salts Ni(NO3)2·6H2O, N4O 10Ru, Mg(NO3)2·6H2O and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water (referred to as solution A). In the quaternary metal salt solution, the content of Ni was 7 wt%, the content of Ru was 600 ppm, and (Ni 2+ +Mg 2+ ):Al 3+ The molar ratio is 3: 1. At the same time, 250 mL of a 0.4 mol / L NaOH solution (referred to as solution B) was also prepared.

[0048] Solution A and solution B were slowly added to the three-necked flask at the same time and stirred vigorously. During the mixing process, the temperature was maintained at 65°C and the pH of the solution was maintained at 10±0.5. After the addition was completed, the temperature of the reaction solution was maintained at 65°C and continued to be stirred for 16 hours, then filtered and washed with ultrapure water several times until the pH value of the washing solution was 7. The sample was then dried in still air at 100°C for 12 hours. The dried sample was immersed in a 2 mol / L Na2CO3 solution at room temperature and stirred for 16 hours. Finally, the sample obtained after filtration and drying was reduced at 650°C for 4 hours under pure hydrogen conditions to obtain a Ni-Ru single atom alloy catalyst.

[0049] Example 5

[0050] First, 100 mL of 0.4 mol / L Na2CO3 aqueous solution was added to a three-necked flask, and then four metal salts Ni(NO3)2·6H2O, PdCl2, Mg(NO3)2·6H2O and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water (referred to as solution A). In the quaternary metal salt solution, the content of Ni was 10 wt%, the content of Pd was 700 ppm, and (Ni 2+ +Mg 2+ ):Al 3+ The molar ratio is 3: 1. At the same time, 250 mL of a 0.4 mol / L NaOH solution (referred to as solution B) was also prepared.

[0051] Solution A and solution B were slowly added to the three-necked flask at the same time and stirred vigorously. During the mixing process, the temperature was maintained at 65°C and the pH of the solution was maintained at 10±0.5. After the addition was completed, the temperature of the reaction solution was maintained at 65°C and continued to be stirred for 16 hours, then filtered and washed with ultrapure water several times until the pH value of the washing solution was 7. The sample was then dried in still air at 100°C for 12 hours. The dried sample was immersed in a 2mol / L Na2CO3 solution at room temperature and stirred for 16 hours. Finally, the sample obtained after filtration and drying was reduced at 850°C for 4 hours under pure hydrogen conditions to obtain a Ni-Pd single-atom alloy catalyst.

[0052] Example 6

[0053] First, 100 mL of 0.4 mol / L Na2CO3 aqueous solution was added to a three-necked flask, and then four metal salts Ni(NO3)2·6H2O, C2H4N4O6Pd, Mg(NO3)2·6H2O and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water (referred to as solution A). In the quaternary metal salt solution, the content of Ni was 10 wt%, the content of Pd was 900 ppm, and (Ni 2+ +Mg 2+ ):Al 3+ The molar ratio is 3: 1. At the same time, 250 mL of a 0.4 mol / L NaOH solution (referred to as solution B) was also prepared.

[0054] Solution A and solution B were slowly added to the three-necked flask at the same time and stirred vigorously. During the mixing process, the temperature was maintained at 65°C and the pH of the solution was maintained at 10±0.5. After the addition was completed, the temperature of the reaction solution was maintained at 65°C and continued to be stirred for 16 hours, then filtered and washed with ultrapure water several times until the pH value of the washing solution was 7. The sample was then dried in still air at 100°C for 12 hours. The dried sample was immersed in a 2mol / L Na2CO3 solution at room temperature and stirred for 16 hours. Finally, the sample obtained after filtration and drying was reduced at 800°C for 4 hours under pure hydrogen conditions to obtain a Ni-Pd single-atom alloy catalyst.

[0055] Example 7

[0056] First, 100 mL of 0.4 mol / L Na2CO3 aqueous solution was added to a three-necked flask, and then four metal salts Ni(NO3)2·6H2O, RhCl3·3H2O, Mg(NO3)2·6H2O and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water (referred to as solution A). In the quaternary metal salt solution, the content of Ni was 10 wt%, the content of Rh was 500 ppm, and (Ni 2+ +Mg 2+ ):Al 3+ The molar ratio is 3: 1. At the same time, 250 mL of a 0.4 mol / L NaOH solution (referred to as solution B) was also prepared.

[0057] Solution A and solution B were slowly added to the three-necked flask at the same time and stirred vigorously. During the mixing process, the temperature was maintained at 65°C and the pH of the solution was maintained at 10±0.5. After the addition was completed, the temperature of the reaction solution was maintained at 65°C and continued to be stirred for 16 hours, then filtered and washed with ultrapure water several times until the pH value of the washing solution was 7. The sample was then dried in still air at 100°C for 12 hours. The dried sample was immersed in a 2mol / L Na2CO3 solution at room temperature and stirred for 16 hours. Finally, the sample obtained after filtration and drying was reduced at 850°C for 4 hours under pure hydrogen conditions to obtain a Ni-Rh single atom alloy catalyst.

[0058] Example 8

[0059] First, 100 mL of 0.4 mol / L Na2CO3 aqueous solution was added into a three-necked flask, and then four metal salts Ni(NO3)2·6H2O, C 12 H 18 Ir3O 13 ·C2H3O2·3H2O, Mg(NO3)2·6H2O and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water (referred to as solution A). In the quaternary metal salt solution, the content of Ni was 10 wt%, the content of Ir was 500 ppm, and (Ni 2+ +Mg 2+ ):Al 3+ The molar ratio is 3: 1. At the same time, 250 mL of a 0.4 mol / L NaOH solution (referred to as solution B) was also prepared.

[0060] Solution A and solution B were slowly added dropwise to a three-necked flask at the same time and stirred vigorously. During the mixing process, the temperature was maintained at 65°C and the pH of the solution was maintained at 10±0.5. After the addition was completed, the temperature of the reaction solution was maintained at 65°C and continued to be stirred for 16 hours, then filtered and washed with ultrapure water several times until the pH value of the washing solution was 7. The sample was then dried in still air at 100°C for 12 hours. The dried sample was immersed in a 2 mol / L Na2CO3 solution at room temperature and stirred for 16 hours. Finally, the sample obtained after filtration and drying was reduced at 850°C for 4 hours under pure hydrogen conditions to obtain a Ni-Ir single atom alloy catalyst.

[0061] Example 9

[0062] First, 100 mL of 0.4 mol / L Na2CO3 aqueous solution was added to a three-necked flask, and then four metal salts Ni(NO3)2·6H2O, AgNO3, Mg(NO3)2·6H2O and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water (referred to as solution A). In the quaternary metal salt solution, the content of Ni was 10 wt%, the content of Ag was 500 ppm, and (Ni 2+ +Mg 2+ ):Al 3+ The molar ratio is 3: 1. At the same time, 250 mL of a 0.4 mol / L NaOH solution (referred to as solution B) was also prepared.

[0063] Solution A and solution B were slowly added to the three-necked flask at the same time and stirred vigorously. During the mixing process, the temperature was maintained at 65°C and the pH of the solution was maintained at 10±0.5. After the addition was completed, the temperature of the reaction solution was maintained at 65°C and continued to be stirred for 16 hours, then filtered and washed with ultrapure water several times until the pH value of the washing solution was 7. The sample was then dried in still air at 100°C for 12 hours. The dried sample was immersed in a 2 mol / L Na2CO3 solution at room temperature and stirred for 16 hours. Finally, the sample obtained after filtration and drying was reduced at 850°C for 4 hours under pure hydrogen conditions to obtain a Ni-Ag single atom alloy catalyst.

[0064] Example 10

[0065] First, 100 mL of 0.4 mol / L Na2CO3 aqueous solution was added to a three-necked flask, and then four metal salts Ni(NO3)2·6H2O, AuCl4H, Mg(NO3)2·6H2O and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water (referred to as solution A). In the quaternary metal salt solution, the content of Ni was 10 wt%, the content of Au was 500 ppm, and (Ni 2+ +Mg 2+ ):Al 3+ The molar ratio is 3: 1. At the same time, 250 mL of a 0.4 mol / L NaOH solution (referred to as solution B) was also prepared.

[0066] Solution A and solution B were slowly added to the three-necked flask at the same time and stirred vigorously. During the mixing process, the temperature was maintained at 65°C and the pH of the solution was maintained at 10±0.5. After the addition was completed, the temperature of the reaction solution was maintained at 65°C and continued to be stirred for 16 hours, then filtered and washed with ultrapure water several times until the pH value of the washing solution was 7. The sample was then dried in still air at 100°C for 12 hours. The dried sample was immersed in a 2 mol / L Na2CO3 solution at room temperature and stirred for 16 hours. Finally, the sample obtained after filtration and drying was reduced at 850°C for 4 hours under pure hydrogen conditions to obtain a Ni-Au single atom alloy catalyst.

[0067] Embodiment 11

[0068] First, 100 mL of 0.4 mol / L Na2CO3 aqueous solution was added to a three-necked flask, and then four metal salts Ni(NO3)2·6H2O, Fe2(SO4)3, Mg(NO3)2·6H2O and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water (referred to as solution A). In the quaternary metal salt solution, the content of Ni was 10 wt%, the content of Fe was 0.5 wt%, and (Ni 2+ +Mg 2+ ):Al 3+ The molar ratio is 3: 1. At the same time, 250 mL of a 0.4 mol / L NaOH solution (referred to as solution B) was also prepared.

[0069] Solution A and solution B were slowly added to the three-necked flask at the same time and stirred vigorously. During the mixing process, the temperature was maintained at 65°C and the pH of the solution was maintained at 10±0.5. After the addition was completed, the temperature of the reaction solution was maintained at 65°C and continued to be stirred for 16 hours, then filtered and washed with ultrapure water several times until the pH value of the washing solution was 7. The sample was then dried in still air at 100°C for 12 hours. The dried sample was immersed in a 2 mol / L Na2CO3 solution at room temperature and stirred for 16 hours. Finally, the sample obtained after filtration and drying was reduced at 850°C for 4 hours under pure hydrogen conditions to obtain a Ni-Fe single atom alloy catalyst.

[0070] Example 12

[0071] First, 100 mL of 0.4 mol / L Na2CO3 aqueous solution was added to a three-necked flask, and then four metal salts Ni(NO3)2·6H2O, Co(NO3)2·6H2O, Mg(NO3)2·6H2O, and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water (referred to as solution A). In the quaternary metal salt solution, the content of Ni was 10 wt%, the content of Co was 0.5 wt%, and (Ni 2++Mg 2+ ):Al 3+ The molar ratio is 3: 1. At the same time, 250 mL of a 0.4 mol / L NaOH solution (referred to as solution B) was also prepared.

[0072] Solution A and solution B were slowly added to the three-necked flask at the same time and stirred vigorously. During the mixing process, the temperature was maintained at 65°C and the pH of the solution was maintained at 10±0.5. After the addition was completed, the temperature of the reaction solution was maintained at 65°C and continued to be stirred for 16 hours, then filtered and washed with ultrapure water several times until the pH value of the washing solution was 7. The sample was then dried in still air at 100°C for 12 hours. The dried sample was immersed in a 2mol / L Na2CO3 solution at room temperature and stirred for 16 hours. Finally, the sample obtained after filtration and drying was reduced at 850°C for 4 hours under pure hydrogen conditions to obtain a Ni-Co single atom alloy catalyst.

[0073] Embodiment 13

[0074] First, 100 mL of 0.4 mol / L Na2CO3 aqueous solution was added to a three-necked flask, and then four metal salts Ni(NO3)2·6H2O, Cu(NO3)2, Mg(NO3)2·6H2O and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water (referred to as solution A). In the quaternary metal salt solution, the content of Ni was 10 wt%, the content of Cu was 0.5 wt%, and (Ni 2+ +Mg 2+ ):Al 3+ The molar ratio is 3: 1. At the same time, 250 mL of a 0.4 mol / L NaOH solution (referred to as solution B) was also prepared.

[0075] Solution A and solution B were slowly added to the three-necked flask at the same time and stirred vigorously. During the mixing process, the temperature was maintained at 65°C and the pH of the solution was maintained at 10±0.5. After the addition was completed, the temperature of the reaction solution was maintained at 65°C and continued to be stirred for 16 hours, then filtered and washed with ultrapure water several times until the pH value of the washing solution was 7. The sample was then dried in still air at 100°C for 12 hours. The dried sample was immersed in a 2 mol / L Na2CO3 solution at room temperature and stirred for 16 hours. Finally, the sample obtained after filtration and drying was reduced at 850°C for 4 hours under pure hydrogen conditions to obtain a Ni-Cu single atom alloy catalyst.

[0076] Embodiment 14

[0077] First, 100 mL of 0.4 mol / L Na2CO3 aqueous solution was added to a three-necked flask, and then four metal salts Ni(NO3)2·6H2O, ZnCl2, Mg(NO3)2·6H2O and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water (referred to as solution A). In the quaternary metal salt solution, the content of Ni was 10 wt%, the content of Zn was 0.5 wt%, and (Ni 2+ +Mg 2+ ):Al 3+ The molar ratio is 3: 1. At the same time, 250 mL of a 0.4 mol / L NaOH solution (referred to as solution B) was also prepared.

[0078] Solution A and solution B were slowly added to the three-necked flask at the same time and stirred vigorously. During the mixing process, the temperature was maintained at 65°C and the pH of the solution was maintained at 10±0.5. After the addition was completed, the temperature of the reaction solution was maintained at 65°C and continued to be stirred for 16 hours, then filtered and washed with ultrapure water several times until the pH value of the washing solution was 7. The sample was then dried in still air at 100°C for 12 hours. The dried sample was immersed in a 2mol / L Na2CO3 solution at room temperature and stirred for 16 hours. Finally, the sample obtained after filtration and drying was reduced at 850°C for 4 hours under pure hydrogen conditions to obtain a Ni-Zn single atom alloy catalyst.

[0079] Embodiment 15

[0080] First, 100 mL of 0.4 mol / L Na2CO3 aqueous solution was added to a three-necked flask, and then four metal salts Ni(NO3)2·6H2O, Ga(NO3)3·xH2O, Mg(NO3)2·6H2O and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water (referred to as solution A). In the quaternary metal salt solution, the content of Ni was 10 wt%, the content of Ga was 0.5 wt%, and (Ni 2+ +Mg 2+ ):Al 3+ The molar ratio is 3: 1. At the same time, 250 mL of a 0.4 mol / L NaOH solution (referred to as solution B) was also prepared.

[0081] Solution A and solution B were slowly added to the three-necked flask at the same time and stirred vigorously. During the mixing process, the temperature was maintained at 65°C and the pH of the solution was maintained at 10±0.5. After the addition was completed, the temperature of the reaction solution was maintained at 65°C and continued to be stirred for 16 hours, then filtered and washed with ultrapure water several times until the pH value of the washing solution was 7. The sample was then dried in still air at 100°C for 12 hours. The dried sample was immersed in a 2 mol / L Na2CO3 solution at room temperature and stirred for 16 hours. Finally, the sample obtained after filtration and drying was reduced at 850°C for 4 hours under pure hydrogen conditions to obtain a Ni-Ga single atom alloy catalyst.

[0082] Example 16

[0083] First, 100 mL of 0.4 mol / L Na2CO3 aqueous solution was added to a three-necked flask, and then four metal salts Ni(NO3)2·6H2O, In(NO3)3, Mg(NO3)2·6H2O and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water (referred to as solution A). In the quaternary metal salt solution, the content of Ni was 10 wt%, the content of In was 0.5 wt%, and (Ni 2+ +Mg 2+ ):Al 3+ The molar ratio is 3: 1. At the same time, 250 mL of a 0.4 mol / L NaOH solution (referred to as solution B) was also prepared.

[0084] Solution A and solution B were slowly added to the three-necked flask at the same time and stirred vigorously. During the mixing process, the temperature was maintained at 65°C and the pH of the solution was maintained at 10±0.5. After the addition was completed, the temperature of the reaction solution was maintained at 65°C and continued to be stirred for 16 hours, then filtered and washed with ultrapure water several times until the pH value of the washing solution was 7. The sample was then dried in still air at 100°C for 12 hours. The dried sample was immersed in a 2mol / L Na2CO3 solution at room temperature and stirred for 16 hours. Finally, the sample obtained after filtration and drying was reduced at 850°C for 4 hours under pure hydrogen conditions to obtain a Ni-In single atom alloy catalyst.

[0085] Embodiment 17

[0086] First, 100 mL of 0.4 mol / L Na2CO3 aqueous solution was added to a three-necked flask, and then four metal salts Ni(NO3)2·6H2O, Mn(NO3)2, Mg(NO3)2·6H2O and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water (referred to as solution A). In the quaternary metal salt solution, the content of Ni was 10 wt%, the content of Mn was 0.5 wt%, and (Ni 2+ +Mg2+ ):Al 3+ The molar ratio is 3: 1. At the same time, 250 mL of a 0.4 mol / L NaOH solution (referred to as solution B) was also prepared.

[0087] Solution A and solution B were slowly added to the three-necked flask at the same time and stirred vigorously. During the mixing process, the temperature was maintained at 65°C and the pH of the solution was maintained at 10±0.5. After the addition was completed, the temperature of the reaction solution was maintained at 65°C and continued to be stirred for 16 hours, then filtered and washed with ultrapure water several times until the pH value of the washing solution was 7. The sample was then dried in still air at 100°C for 12 hours. The dried sample was immersed in a 2mol / L Na2CO3 solution at room temperature and stirred for 16 hours. Finally, the sample obtained after filtration and drying was reduced at 850°C for 4 hours under pure hydrogen conditions to obtain a Ni-Mn single atom alloy catalyst.

[0088] Embodiment 18

[0089] First, 100 mL of 0.4 mol / L Na2CO3 aqueous solution was added to a three-necked flask, and then four metal salts Ni(NO3)2·6H2O, Bi(NO3)3, Mg(NO3)2·6H2O and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water (referred to as solution A). In the quaternary metal salt solution, the content of Ni was 10 wt%, the content of Bi was 0.5 wt%, and (Ni 2+ +Mg 2+ ):Al 3+ The molar ratio is 3: 1. At the same time, 250 mL of a 0.4 mol / L NaOH solution (referred to as solution B) was also prepared.

[0090] Solution A and solution B were slowly added to the three-necked flask at the same time and stirred vigorously. During the mixing process, the temperature was maintained at 65°C and the pH of the solution was maintained at 10±0.5. After the addition was completed, the temperature of the reaction solution was maintained at 65°C and continued to be stirred for 16 hours, then filtered and washed with ultrapure water several times until the pH value of the washing solution was 7. The sample was then dried in still air at 100°C for 12 hours. The dried sample was immersed in a 2 mol / L Na2CO3 solution at room temperature and stirred for 16 hours. Finally, the sample obtained after filtration and drying was reduced at 850°C for 4 hours under pure hydrogen conditions to obtain a Ni-Bi single atom alloy catalyst.

[0091] Embodiment 19

[0092] First, 100 mL of 0.4 mol / L Na2CO3 aqueous solution was added to a three-necked flask, and then four metal salts Ni(NO3)2·6H2O, Cd(NO3)2·4H2O, Mg(NO3)2·6H2O, and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water (referred to as solution A). In the quaternary metal salt solution, the content of Ni was 10 wt%, the content of Cd was 0.5 wt%, and (Ni 2+ +Mg 2+ ):Al 3+ The molar ratio is 3: 1. At the same time, 250 mL of a 0.4 mol / L NaOH solution (referred to as solution B) was also prepared.

[0093] Solution A and solution B were slowly added to the three-necked flask at the same time and stirred vigorously. During the mixing process, the temperature was maintained at 65°C and the pH of the solution was maintained at 10±0.5. After the addition was completed, the temperature of the reaction solution was maintained at 65°C and continued to be stirred for 16 hours, then filtered and washed with ultrapure water several times until the pH value of the washing solution was 7. The sample was then dried in still air at 100°C for 12 hours. The dried sample was immersed in a 2mol / L Na2CO3 solution at room temperature and stirred for 16 hours. Finally, the sample obtained after filtration and drying was reduced at 850°C for 4 hours under pure hydrogen conditions to obtain a Ni-Cd single-atom alloy catalyst.

[0094] Embodiment 20

[0095] First, 100 mL of 0.4 mol / L Na2CO3 aqueous solution was added to a three-necked flask, and then four metal salts Ni(NO3)2·6H2O, SnCl2, Mg(NO3)2·6H2O and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water (referred to as solution A). In the quaternary metal salt solution, the content of Ni was 10 wt%, the content of Sn was 0.5 wt%, and (Ni 2+ +Mg 2+ ):Al 3+ The molar ratio is 3: 1. At the same time, 250 mL of a 0.4 mol / L NaOH solution (referred to as solution B) was also prepared.

[0096] Solution A and solution B were slowly added to the three-necked flask at the same time and stirred vigorously. During the mixing process, the temperature was maintained at 65°C and the pH of the solution was maintained at 10±0.5. After the addition was completed, the temperature of the reaction solution was maintained at 65°C and continued to be stirred for 16 hours, then filtered and washed with ultrapure water several times until the pH value of the washing solution was 7. The sample was then dried in still air at 100°C for 12 hours. The dried sample was immersed in a 2mol / L Na2CO3 solution at room temperature and stirred for 16 hours. Finally, the sample obtained after filtration and drying was reduced at 850°C for 4 hours under pure hydrogen conditions to obtain a Ni-Sn single atom alloy catalyst.

[0097] Comparative Example 1 Preparation of Ni-LDH Catalyst

[0098] First, 100 mL of 0.4 mol / L Na2CO3 aqueous solution was added to a three-necked flask, and then three metal salts Ni(NO3)2·6H2O, Mg(NO3)2·6H2O and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water (referred to as solution A). The content of Ni in the ternary metal salt solution was 10 wt%, (Ni 2+ +Mg 2+ ):Al 3+ The molar ratio is 3: 1. At the same time, 250 mL of a 0.4 mol / L NaOH solution (referred to as solution B) was also prepared.

[0099] Solution A and solution B were slowly added to the three-necked flask at the same time and stirred vigorously. During the mixing process, the temperature was maintained at 65°C and the pH of the solution was maintained at 10±0.5. After the addition was completed, the temperature of the reaction solution was maintained at 65°C and continued to be stirred for 16 hours, then filtered and washed with ultrapure water several times until the pH value of the washing solution was 7. The sample was then dried in still air at 100°C for 12 hours. The dried sample was immersed in a 2 mol / L Na2CO3 solution at room temperature and stirred for 16 hours. Finally, the sample obtained after filtration and drying was reduced at 850°C for 4 hours under pure hydrogen conditions to obtain a Ni monometallic catalyst.

[0100] Comparative Example 2 Preparation of Pt-LDH Catalyst

[0101] First, 100 mL of 0.4 mol / L Na2CO3 aqueous solution was added to a three-necked flask, and then three metal salts H2PtCl4, Mg(NO3)2·6H2O, and Al(NO3)3·9H2O were dissolved in 100 mL of ultrapure water (referred to as solution A). In the ternary metal salt solution, the content of Pt was 500 ppm, and the content of Mg was 1.3 ppm. 2+ :Al 3+The molar ratio is 3: 1. At the same time, 250 mL of a 0.4 mol / L NaOH solution (referred to as solution B) was also prepared.

[0102] Solution A and solution B were slowly added to the three-necked flask at the same time and stirred vigorously. During the mixing process, the temperature was maintained at 65°C and the pH of the solution was maintained at 10±0.5. After the addition was completed, the temperature of the reaction solution was maintained at 65°C and continued to be stirred for 16 hours, then filtered and washed with ultrapure water several times until the pH value of the washing solution was 7. The sample was then dried in still air at 100°C for 12 hours. The dried sample was immersed in a 2 mol / L Na2CO3 solution at room temperature and stirred for 16 hours. Finally, the sample obtained after filtration and drying was reduced at 850°C for 4 hours under pure hydrogen conditions to obtain a Pt monometallic catalyst.

[0103] like Figure 2 As shown, the Pt species in the catalyst prepared by this method exists in the form of Pt-Pt coordination bonds, that is, it exists in the catalyst in the form of Pt particles rather than in the form of single atoms.

[0104] Comparative Example 3 Preparation of Ni / CNT Catalyst

[0105] 1g of carbon nanotubes was used as a carrier and as a mass reference. Ni(NO3)2·6H2O was weighed at a ratio of 10wt% Ni content and ultrasonically dissolved in 1mL ultrapure water to obtain a Ni metal salt solution. 1g of carbon nanotubes was added to the metal Ni salt solution and stirred with a glass rod to fully mix the carrier and the solution. The impregnated catalyst precursor was aged at room temperature for 12 hours and then dried in a 120°C oven for 12 hours. In a reducing atmosphere of pure hydrogen, the catalyst was reduced at 400°C for 4 hours to obtain a Ni / CNT single metal catalyst.

[0106] Example 21 Catalyst Performance Evaluation

[0107] A methanol solution of DADNP was prepared in a 1000 mL volumetric flask as a reaction raw material at a concentration of 0.05 mg / mL. 100 mg of a noble metal single-atom alloy catalyst (or 300 mg of a non-noble metal single-atom alloy catalyst) and 60 mL of a methanol solution of DADNP were added to a reactor, the reactor was sealed, and the air was purged with argon for several times. The reaction was carried out at low temperatures to reduce the formation of excessive hydrogenation products. When the reaction temperature stabilized to the set value, H2 was charged into the reactor, and stirring was turned on and timing was started. The stirring rate was 800 rpm. After 240 min of reaction, sampling was performed, and the samples were immediately analyzed by ultra-high performance liquid chromatography.

[0108] It should be noted that the chromatograph used was Waters Acquity UPLC, the chromatographic conditions were: column temperature: 25°C, flow rate: 0.4 mL / min, mobile phase ratio: methanol: water (0.05 M tetrabutylammonium bromide, 0.025 M NH4H2PO4) = 40:60, and detection wavelength: 237 nm.

[0109] The Ni-LDH, Pt-LDH and Ni / CNT prepared by the methods of Comparative Examples 1 to 3 were used to compare and evaluate the catalyst. The catalytic performance of the catalyst of the present invention for the selective hydrogenation of 2,6-diamino-3,5-dinitropyridine to produce 2,3,5,6-tetraaminopyridine was evaluated by testing the 2,6-diamino-3,5-dinitropyridine (DADNP) conversion rate and 2,3,5,6-tetraaminopyridine (TAP) selectivity and yield of the catalysts prepared in Examples 1 to 20, Ni-LDH, Pt-LDH and Ni / CNT catalysts.

[0110] in:

[0111] In the reaction of selective hydrogenation of 2,6-diamino-3,5-dinitropyridine (DADNP) to prepare 2,3,5,6-tetraaminopyridine (TAP), the calculation formulas of DADNP conversion, TAP selectivity and yield are as follows:

[0112] X(%)=(n 初始DADNP -n 反应后DADNP ) / n 初始DADNP ×100%

[0113] S i (%)=(n 组分i ×A i ) / n 初始DADNP ×100%

[0114] Y i (%) = X × S i ×100%

[0115] Wherein, X represents the conversion rate of 2,6-diamino-3,5-dinitropyridine, in %;

[0116] n 初始DADNP 、n 反应后DADNP Respectively represent the amount of 2,6-diamino-3,5-dinitropyridine at the beginning and after the reaction, in mol;

[0117] S i It represents the selectivity of component i, in %;

[0118] n 组分i It represents the amount of substance of component i after the reaction, in mol;

[0119] A i Indicates the number of carbon atoms contained in the molecule of component i;

[0120] Y i It represents the yield of component i in %.

[0121] Table 1. Evaluation results of Ni-M single atom alloy catalyst DADNP selective hydrogenation reaction

[0122]

[0123]

[0124] It can be seen from Table 1 that when the above 17 Ni-M single atom alloy catalysts loaded on the carrier of the present invention catalyze the DADNP hydrogenation reaction, DADNP is basically converted completely; the selectivity of TAP is greater than 93%, which is significantly better than Ni-LDH, Pt-LDH and Ni / CNT catalysts.

[0125] Example 22 Catalyst Stability Evaluation

[0126] The NiPt catalyst prepared in Example 1, the NiRu catalyst prepared in Example 3, and the NiCu catalyst prepared in Example 13 were randomly selected, and the reaction was carried out in cycles for multiple times according to the catalytic performance test method of Example 21. The stability of the catalysts was evaluated respectively, and the data results of X (DADNP), S (TAP) and Y (TAP) are shown in Tables 2 to 4.

[0127] Table 2. NiPt catalyst stability evaluation

[0128] Cycle times X(DADNP)(%) S(TAP)(%) Y(TAP)(%) 1 100 99.21 99.21 2 100 99.20 99.20 3 100 99.05 99.05 5 100 98.73 98.73 10 100 98.44 98.44

[0129] As can be seen from Table 2, the supported Ni-M single atom alloy catalyst NiPt prepared in Example 1, after 10 cycles with a reaction time of 240 min each, the conversion rate of 2,6-diamino-3,5-dinitropyridine is still maintained at 100%, the selectivity of 2,3,5,6-tetraaminopyridine is maintained at more than 98.44%, and the yield of 2,3,5,6-tetraaminopyridine is maintained at more than 98.44%.

[0130] The above results show that the supported Ni-M single atom alloy catalyst NiPt prepared in Example 1 has good stability.

[0131] Table 3. Evaluation of NiRu catalyst stability

[0132] Cycle times X(DADNP)(%) S(TAP)(%) Y(TAP)(%) 1 100 99.07 99.07 2 100 98.90 98.90 3 100 98.85 98.85 5 100 98.80 98.80 10 100 98.23 98.23

[0133] As can be seen from Table 3, the supported Ni-M single atom alloy catalyst NiRu prepared in Example 3, after 10 cycles with a reaction time of 240 min each, the conversion rate of 2,6-diamino-3,5-dinitropyridine is still maintained at 100%, the selectivity of 2,3,5,6-tetraaminopyridine is maintained at more than 98.23%, and the yield of 2,3,5,6-tetraaminopyridine is maintained at more than 98.23%.

[0134] The above results show that the supported Ni-M single atom alloy catalyst NiRu prepared in Example 2 has good stability.

[0135] Table 4. Evaluation of NiCu catalyst stability

[0136] Cycle times X(DADNP)(%) S(TAP)(%) Y(TAP)(%) 1 96.25 94.01 90.48 2 95.45 93.92 89.65 3 94.12 92.12 86.70 5 93.77 91.78 86.06 10 92.27 90.17 83.20

[0137] As can be seen from Table 4, the supported Ni-M single atom alloy catalyst NiCu prepared in Example 13, after 10 cycles with a reaction time of 240 min each, the conversion rate of 2,6-diamino-3,5-dinitropyridine is still maintained at more than 92.27%, the selectivity of 2,3,5,6-tetraaminopyridine is maintained at more than 90.17%, and the yield of 2,3,5,6-tetraaminopyridine is maintained at more than 83.20%.

[0138] The above results show that although the stability of the supported Ni-M single atom alloy catalyst NiCu prepared in Example 13 is relatively weaker than that in Examples 1 and 3, it still has good stability.

[0139] In summary, the Ni-M single atom alloy catalyst of the present invention has good stability and long service life.

[0140] This application is described in detail for the purpose of enabling those skilled in the art to understand the contents of this application and implement them. This is not intended to limit the scope of protection of this application. Any equivalent changes or modifications made according to the spirit of this application should be included in the scope of protection of this application.

Claims

1. An application of a Ni-M single atom alloy catalyst, characterized in that: The Ni-M single-atom alloy catalyst is used for the reaction of selectively hydrogenating 2,6-diamino-3,5-dinitropyridine to prepare 2,3,5,6-tetraaminopyridine; The catalyst carrier is a magnesium aluminum metal mixed oxide MgAlO X , and loads a first metal Ni and a second metal M; the second metal M is selected from one of the noble metals Pt, Ru, Pd, Rh, Ir, Ag and Au, or one of the non-noble metals Fe, Co, Cu, Zn, Ga, In, Mn, Bi, Cd, Sn; The preparation method of the catalyst comprises the following steps: (1) Using metal salts of Ni, M, Mg, and Al as metal precursors to prepare a mixed metal salt solution; wherein the second metal M is selected from one of the noble metals Pt, Ru, Pd, Rh, Ir, Ag, and Au, or one of the non-noble metals Fe, Co, Cu, Zn, Ga, In, Mn, Bi, Cd, and Sn; (2) adding the mixed metal salt solution to a precipitant, and preparing a Ni / M / Mg / Al quaternary layered hydroxide material Q by a coprecipitation method; (3) The Ni / M / Mg / Al quaternary layered hydroxide material Q is thermally reduced to obtain a supported Ni-M single atom alloy catalyst; The step (3) further includes an ion exchange step of the Ni / M / Mg / Al quaternary layered hydroxide material Q before the thermal reduction step: The Ni / M / Mg / Al quaternary layered hydroxide material Q is added to an ion exchanger, stirred at room temperature for a period of time, filtered, washed, dried, and then subjected to a thermal reduction step to obtain a supported Ni-M single atom alloy catalyst; Wherein, the ion exchanger is selected from Na2CO3 solution, NaHCO3 solution, K2CO3 solution or KHCO3 solution.

2. The use of the Ni-M single atom alloy catalyst according to claim 1, characterized in that: In the step (1), the metal salts of Ni, Mg and Al are nickel nitrate hexahydrate, magnesium nitrate hexahydrate and aluminum nitrate nonahydrate respectively; the precursor species of the second metal M is selected from H2PtCl4, RuCl3, Fe2(SO4)3, Co(NO3)2·6H2O, Cu(NO3)2, ZnCl2, Ga(NO3)3·xH2O, PdCl2, RhCl3·3H2O, C 12 H 18 Ir3O 13 ·C2H3O2·3H2O, In(NO3)3, AgNO3, AuCl4H, Mn(NO3)2, Bi(NO3)3, Cd(NO3)2·4H2O, SnCl2, Na2[PtCl6]·6H2O, N4O 10 One or more of Ru, C2H4N4O6Pd.

3. The use of the Ni-M single atom alloy catalyst according to claim 1, characterized in that: In the step (1), the content of Ni in the mixed metal salt solution is 1 wt% to 30 wt%, and the content of M is 50 ppm to 1 wt%.

4. The use of the Ni-M single atom alloy catalyst according to claim 1, characterized in that: The content of Ni in the mixed metal salt solution is 7 wt% to 15 wt%; When the M is selected from noble metals, the content of M is 50 ppm to 0.5 wt%; When the M is selected from non-precious metals, the content of M is 0.1 wt% to 1 wt%.

5. The use of the Ni-M single atom alloy catalyst according to claim 1, characterized in that: The content of Ni in the mixed metal salt solution is 10 wt %; When the M is selected from noble metals, the content of M is 50 ppm to 0.1 wt%; When the M is selected from non-precious metals, the content of M is 0.1 wt% to 0.5 wt%.

6. The use of the Ni-M single atom alloy catalyst according to claim 1, characterized in that: The content of Ni in the mixed metal salt solution is 10 wt %; When the M is selected from a noble metal, the content of M is 500 ppm; When the M is selected from non-precious metals, the content of M is 0.5 wt %.

7. The use of the Ni-M single atom alloy catalyst according to claim 1, characterized in that: In the step (2), a pH regulator and the mixed metal salt solution are added to the precipitant under stirring conditions, the temperature of the reaction system is maintained at 60 to 70° C., and the pH value of the reaction system is controlled to be 10±0.

5. After the addition is completed, the reaction is continued to be stirred for 18 to 36 hours, and finally filtered, washed, and dried to obtain the Ni / M / Mg / Al quaternary layered hydroxide material Q.

8. The use of the Ni-M single atom alloy catalyst according to claim 7, characterized in that: The precipitant is selected from Na2CO3 solution, NaHCO3 solution, K2CO3 solution or KHCO3 solution; the pH regulator is selected from NaOH solution, NH3·H2O or KOH solution.

9. The use of the Ni-M single atom alloy catalyst according to claim 1, characterized in that: In the step (3), the temperature of the thermal reduction is 600-950° C., the reduction time is 2-10 hours, and the reduction gas is pure hydrogen.

Citation Information

Patent Citations

  • PdM monatomic alloy catalyst for acetylene selective hydrogenation reaction and preparation method of PdM monatomic alloy catalyst

    CN115532269A

  • Supported monatomic alloy catalyst as well as preparation method and application thereof

    CN116196937A